تأثير التسويق بالمحتوى عبر مواقع التواصل الاجتماعي في تعزيز النية الشرائية - قريبيز، حسام الدين; ساحي ،مصطفى (جامعة الوادي University of Eloued, 2024)
This study aims to shed light on the impact of content marketing through social media platforms on the purchasing intention of a sample of subscribers to the Royal Mill company should be present in good content, including (Relevance, Credibility, Value, And Attractiveness). The survey was used as a data collection tool with a sample size of 386 subscribers. Data analysis was performed using the Statistical Package for the Social Sciences (SPSS V26). The study concluded the presence of a statistically significant positive relationship between the combined elements of content marketing and the enhancement of purchasing intention among the study sample.
The impact of content marketing through social media platforms on the purchasing intention: A field study of subscribers on social media platforms of Royal Mill company in Laghouat
Keywords: التسويق بالمحتوى; الملائمة; المصداقية; القيمة،الجاذبية; النية الشرائية; Content Marketing; relevance; credibility